Tecnologia da Informação Verde: Estudo à luz da teoria Crença-Ação-Resultado - Gabriela Figueiredo Dias; Anatália Saraiva Martins Ramos; Rômulo Andrade de Souza Neto; Evangelina de Mello Bastos (RAE: Revista de Administração de Empresas, 2017)
This study aims to understand how institutional pressures and managers’ environmental beliefs influence the adoption of Green Information Technology (Green IT). The theoretical framework of the Belief-Action-Outcome model is used. In a qualitative research approach, data on 10 university IT managers were collected through interviews and a checklist of Green IT practices. Content analysis on the interviews was performed and the responses to the checklist were analyzed by frequency. Analysis results show that the institutional pressure most related to the adoption of Green IT for the interviewees is mimetic. Regarding environmental beliefs, while eight managers expressed concerns about environmental issues, only three reported their own initiatives. Other respondents said they faced barriers such as bureaucratic dysfunctions and lack of management support to propose actions related to Green IT.